The Influence of the Work Environment, Work Motivation, and Work Discipline on Employee Performance at the NTB PUPR Office - Widya Pratiwi; Sulaimiah Sulaimiah (International Journal of Economics, Management and Accounting (IJEMA), 2023)
This study aims to analyze the influence of the Work Environment (X1), Work Motivation (X2) and Work Discipline (X3) on the Performance of Employees at the NTB PUPR Office. The respondents in this study were 50 people. The type of research used is causal associative research with a quantitative approach. The data collection method used is the Census Method. The data analysis technique used is Multiple Linear Regression Analysis processed using SPSS version 16.0. The results showed that: (1) Work Environment has a positive and significant effect on Employee Performance at the PUPR Office in NTB, (2) Work Motivation has a positive and significant effect on Employee Performance at the PUPR Office in NTB (3) Work Discipline has a positive and significant effect on Employee Performance at the PUPR Office NTB. Based on the results of this study, it can be concluded that there is a relationship between the work environment, work motivation and work discipline on the performance of employees at the NTB PUPR Service. If the NTB PUPR Service wants to improve the performance of its employees, the work environment, work motivation and work discipline must be improved.